Co-application of biochar and urea to improve nutrient use efficiency and yield of Oryza sativa L. in tropical acid soil - Maru, Ali (2015)
Excessive use of nitrogen (N) fertilizer in sustaining high rice yields due N dynamics in tropical acid soils has necessitated the exploitation of nutrients addition and retention properties of organic amendment such as chicken litter biochar to increase lowland rice yield and to also reduce N fertilization by improving soil nutrients availability and plant nutrients use efficiency. Biochar (5 t ha-1) and different rates of urea (100%, 75%, 50%, 25% and 0%) only were evaluated in pot and field trials. Selected soil and rice plants physicochemical properties were analyzed using standard procedures. Dielectric response of the soil samples at 20, 40, 55, and 75 days after transplanting of rice plants were determined using an inductance-capacitance-resistance meter HIOKI 3522-50 LCR HiTESTER. Soil nutrients availability, plants nutrients uptake, nutrients use efficiency, crop recovery and agronomic efficiency of applied N, and dry matter yield in the pot and field trials were significantly increased due to co-application of urea with biochar. This was confirmed by the magnitude, shape, and pattern of spectral response of dielectric conductivity and permitivity. Biochar and N rates stimulated the availability of other nutrients especially available P and K. Grain yield of co-application of biochar with 75% urea of the first and second cycles (7.56 t ha-1 and 9.06 t ha-1) were 44.31% and 44.37%, respectively, higher than that of recommended fertilization (4.21 t ha-1 and 5.04 t ha-1). However, the grain yield of co-application of biochar with 100% urea and co-application of biochar with 75% urea in the field trials were not significantly different although coapplication of biochar with 100% urea had 25% more N fertilization than that of coapplication of biochar with 75% urea indicating that, biochar can be used to improve grain yield and as well as reducing N fertilization in rice cultivation on tropical acid soils. Yield of co-application of biochar with 75% urea was higher due to the differences in number of panicles as a result of the effect of biochar on nutrient availability and N use efficiency. Dielectric conductivity and permitivity of soil samples measured before transplanting rice plants were higher than that of soil samples measured during the cultivation of the rice plants due to low moisture content of the soil samples. Dielectric conductivity of the soil samples was dependent on frequency and nutrients concentration in soil solution. Permitivity of the soil samples was inversely proportional to frequency but directly proportional to N concentration in soil solution. The conductivity measured at 1000 Hz to 100000 Hz correlated positively with rice grain yield suggesting that dielectric measurement can be used to estimate rice yield and soil nutrients concentration. This study may only be applicable to tropical acid soils and will contribute to improvement in nutrients use efficiency as well as reducing usage of chemical fertilizers. The use of dielectric technology to measure soil nutrients especially N in rice fields contributes to efficient application and utilization of chemical fertilizers, however, further studies are required to establish a stronger correlation between conductivity and N concentration in rice fields.